2021
DOI: 10.3389/fphar.2020.579330
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution of ACE2 Protein in Syrian Golden Hamster (Mesocricetus auratus) and Its Possible Implications in SARS-CoV-2 Related Studies

Abstract: The Syrian golden hamster (Mesocricetus auratus) has recently been demonstrated as a clinically relevant animal model for SARS-CoV-2 infection. However, lack of knowledge about the tissue-specific expression pattern of various proteins in these animals and the unavailability of reagents like antibodies against this species hampers these models’ optimal use. The major objective of our current study was to analyze the tissue-specific expression pattern of angiotensin-converting enzyme 2, a proven functional rece… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 40 publications
5
39
0
Order By: Relevance
“…Sections were deparaffinized, rehydrated, and subjected to antigen retrieval treatment and serum blocking as reported earlier 22 . Sections were incubated with SARS‐CoV‐2 N protein (Nucleocapsid) (#11‐2003; Abgenex, 1:200) or SOD2/Mn‐SOD (#NB100‐1992; Novus biologicals, 1:100) in a humidified chamber overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sections were deparaffinized, rehydrated, and subjected to antigen retrieval treatment and serum blocking as reported earlier 22 . Sections were incubated with SARS‐CoV‐2 N protein (Nucleocapsid) (#11‐2003; Abgenex, 1:200) or SOD2/Mn‐SOD (#NB100‐1992; Novus biologicals, 1:100) in a humidified chamber overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Collected tissues were processed and sectioned as reported previously 22,24 . Sections were deparaffinized, rehydrated, and subjected to antigen retrieval (Vector Laboratories) treatment for 20 minutes followed by blocking the endogenous peroxidase with 3% hydrogen peroxide in methanol for 20 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a study of Ace2 mRNA in the lung of old (15–17 mo) hamsters showed males had over threefold higher levels of ACE2 than the old females ( 74 ). The authors also found Ace2 mRNA was 37-fold higher in old male hamsters compared with young (2–4 mo) males.…”
Section: Impact Of Biological Sex On Ace2 Expression and Regulationmentioning
confidence: 84%
“…ACE2 and TMPRSS2 are expressed in a wide variety of tissues and have been analyzed using several different genetic techniques 79 . Suprisingly a common denominator in these studies is the high expression of these proteins in extrapulmonary tissues, whereas the virus mainly infects the respiratory tract.…”
Section: Mainmentioning
confidence: 99%